Theoretical study of alternatives for the control of Rupella albinella in rice cultivars (Oryza sativa) - Carrera Coloma, Deivi Alfonso; Sánchez Iznaga, Ángel Lázaro; Marín Gavilanez, Marín Gavilanez; Campi Chang, Gina Maritza; Romero Gaibor, Pedro Pablo; Chichande Marìn, Enzo Xavier (Ingeniería Química y Desarrollo, 2024)
The objective of this work was to investigate theoretically the alternatives for the control of Rupella albinella with biopesticides in rice cultivars. In this work a qualitative research was used, through a documentary research, where information was collected about the alternatives for the control of Rupella albinella in rice cultivars. The information was obtained from publications of scientific articles in indexed journals, books and specialized bibliography available in Google Scholar. The results obtained allowed concluding that: the rice bride (Rupella albinella Cramer) is the most important drilling pest in rice cultivation causing significant losses, and greatly reducing crop yields; the indiscriminate use of chemical pesticides was an alternative used to control important pests in rice cultivation; however, it has caused environmental contamination, animal intoxication and many problems for humans; biological control of pests in rice cultivation is an excellent alternative to reduce the use of chemical pesticides.